Imageable Idioms in Croatian - Broz, Vlatko (Array, 2012)
Imageable idioms are figurative expressions that have associated conventional images or that could call up a conventional scene in the minds of speakers (Lakoff 1987:447). Based on a similar study of figurative expressions in English (Gibbs 1990), this study investigates mental images associated with idiomatic expressions in the Croatian language. The paper presents a cognitive- linguistic study of selected imageable idioms using a sample of 200 native speakers of Croatian. The research starts from the hypothesis that speakers share tacit knowledge about the metaphorical basis for idiomatic expressions that can be recovered by examining speakers' mental images of those expressions. The results of the research show to what extent these mental images overlap and how the speakers account for the motivation of meaning. As expected, a remarkably high degree of consistency in the subjects’ images and responses points to different cognitive mechanisms that motivate the figurative meanings of the selected idioms which feature animals. More importantly, the research manages to explicitly designate what is considered to be a shared tacit knowledge of culture which is in turn reflected in language.